EFFECT OF INSTITUTIONAL OWNERSHIP STRUCTURE, MANAGERIAL OWNERSHIP AND RETURN ON ASSETS (ROA) ON CSR DISCLOSURE WITH FIRM SIZE AS MODERATING VARIABLES IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) 2007-2017 - Hutagaol, Joina (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study was to determine and analyse the effect of institutional ownership structure, managerial ownership, and ROA on CSR disclosure with firm size as a moderating variable in manufacturing companies. The population of this study is manufacturing companies listed on the Stock Exchange with observations for 2007 to 2017. The sample was selected using the purposive sampling method. Data was processed using a statistical regression test method with moderation interactions. The results of this study prove that based on simultaneous test results, institutional ownership structure, managerial ownership, and ROA simultaneously, have a significant effect on CSR disclosure variables. Based on the results of moderation testing with the interaction test firm size has a significant effect in moderating the effect of institutional ownership structure and ROA on CSR disclosure.